Minimization of the energy consumption of soil deformation - Spektor, M. (Journal of terramechanics, 1980)
A study has been performed enabling the minimization of energy consumption during formation of residual strains in cohesive soils, with the aim, for example, of shaping holes. It is demonstrated that minimization of energy consumption is achieved within a definite regime of the soil-implement interaction. This regime is characterized by sequential repetition of the soil's loading and unloading. Within this regime, the controlling factor in ensuring a minimal energy consumption is the magnitude of implement displacement during the soil loading stage. As a result of analytic studies, based on corresponding experimental curves, expressions were obtained for determining the magnitude of displacement at which the minimum value of the soil-deformation energy consumption is reached. It is demonstrated that modern machines with cyclic action (vibration, vibro-impact etc.), intended for the shaping of horizontal and slanted holes for drain arrays and other communication channels, as well as those intended for pile driving, and the shaping of vertical holes for filling piles, operate at regimes characterized by relatively high energy consumption. The development and introduction into service of analogous novel machines based on the results of the present investigation may ensure considerable savings of energy, while simultaneously increasing the productivity of these machines. It is essential to note that the proposed work enables understanding the controversy arising from the opinions of various authors, on the subject of comparison of energy consumption of cyclic and quasi-static processes of soil-implement interaction, thus enabling the elimination of that controversy.